2013
DOI: 10.1111/pce.12186
|View full text |Cite
|
Sign up to set email alerts
|

A new link between stress response and nucleolar function during pollen development in Arabidopsis mediated by AtREN1 protein

Abstract: Heat shock transcription factors (Hsfs) are involved in multiple aspects of stress response and plant growth. However, their role during male gametophyte development is largely unknown, although the generative phase is the most sensitive and critical period in the plant life cycle. Based on a wide screen of T-DNA mutant lines, we identified the atren1 mutation (restricted to nucleolus1) in early male gametophytic gene At1g77570, which has the closest homology to HSFA5 gene, the member of a heat shock transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…We originally considered that heat would induce the expression of these TaHsf genes and that their upregulated expression would lead to the upregulation of other fertility-related genes, thereby ensuring fertility. However, we found that some genes had pollen-specific expression-related binding sites based on our predictions of the ciselements, and previous studies have shown that the AT2G26150 and AT4G13980 genes are critical during pollen reproduction [53,54]. Our analysis of the TaHsfs related to wheat fertility provides a basis for future investigations of the important roles of TaHsfs in the fertility regulation mechanism.…”
Section: Discussionsupporting
confidence: 64%
“…We originally considered that heat would induce the expression of these TaHsf genes and that their upregulated expression would lead to the upregulation of other fertility-related genes, thereby ensuring fertility. However, we found that some genes had pollen-specific expression-related binding sites based on our predictions of the ciselements, and previous studies have shown that the AT2G26150 and AT4G13980 genes are critical during pollen reproduction [53,54]. Our analysis of the TaHsfs related to wheat fertility provides a basis for future investigations of the important roles of TaHsfs in the fertility regulation mechanism.…”
Section: Discussionsupporting
confidence: 64%
“…In plants, transcription factor HSFs are expressed in male reproductive cells during heat stress. In particular, AtHsfA2 (AT2G26150) and AtHsfA5 (AT4G13980) were identified as critical during pollen reproduction in Arabidopsis [67,68]. Five class A Hsfs and three class B Hsfs are up-regulated in rice spikes [40].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the inhibition of RBF or RP gene expression induces a wide variety of plant growth and developmental phenotypes, including embryo lethality, delayed flowering time, and abnormal leaf and root phenotypes (Supplemental Data Sets 3 and 4). Cytological investigations have shown that the nucleolus becomes larger in tormoz (Griffith et al, 2007), nof1 (Harscoët et al, 2010), apum23 (Abbasi et al, 2010), rid2 (Ohbayashi et al, 2011;Shinohara et al, 2014), ren1 (Reňák et al, 2014), la1 (Fleurdepine et al, 2007), and domino1 (Lahmy et al, 2004) compared with wild-type plants. By contrast, the nucleolus is small in fem111 (Portereiko et al, 2006) and disorganized in nuc1 (Pontvianne et al, 2007) plants.…”
Section: Ribosome Response Pathwaymentioning
confidence: 99%